Remote ischemic preconditioning for prevention of contrast-induced nephropathy – A randomized control trial() - Bafna, Akshay Ashok (Indian Heart J, 2020)
BACKGROUND: There is a lack of sufficient data regarding the protective effects of remote ischemic preconditioning (RIPC) in patients at risk of developing contrast-induced nephropathy (CIN). Thus, this study was conducted to determine whether RIPC as an adjunct to standard therapy prevents CIN in high-risk patients undergoing coronary intervention. METHODS: In a single-center, double-blinded, randomized controlled trial, 162 patients who were at risk of CIN received standard hydration combined with RIPC or hydration with sham preconditioning. RIPC was accomplished by four cycles of 5 min ischemia and 5 min reperfusion of the forearm. The primary endpoint was a rise in serum creatinine (>0.5 mg/dL or >25%) from baseline to serum creatinine 48–72 h after contrast administration. RESULTS: Of the 162 patients, 81 were randomly allocated to receive sham preconditioning and 81 to receive RIPC. Significantly reduced serum creatinine levels were observed in patients with a Mehran moderate risk allocated to sham group compared to the RIPC group (0.070 ± 0.16 mg/dL vs. 0.107 ± 0.13 mg/dL, p = 0.001). With regards to the primary endpoint, a significantly higher change in serum creatinine from baseline to 48–72 h was observed in the sham group compared to the RIPC group (0.023 ± 0.2 μmol/L vs −0.064 ± 0.1 μmol/L, p < 0.001). CONCLUSION: RIPC as an alternative to standard therapy, improved serum creatinine levels after contrast administration in patients at risk of CIN. However, present data indicate that RIPC might have beneficial effects in patients with a moderate or high risk of CIN.